A Study on The Quality of Final Exam Items Made by The Teacher at XII Grade Students of Senior High School in Sidrap Regency - Alone Marera (Journal of Biological Science and Education, 2020)
Bad quality of the questions is one of the factors that can lead to errors in the grading of student learning outcomes. It gives a lower students’ score than the appropriate score and will give an impact on school grades (NS). In this case, school grades (NS) have an effect of 40% in determining the passing of national exams (UN). Therefore, this study was conducted to assess the quality of first semester final exam items made by biology class XII teacher based on some aspects; they are the material, construction, and language. In this study, the researcher used purposive sampling technique in order to collect the data. Items were assessed using a multiple-choice item evaluation sheet which has been declared valid by an expert validator. By combining the material aspects of the assessment data, construction, and language, research results obtained in general show that of the 120 items assessed, there are 104 ( 86,7 %) items with excellent criteria and 16 ( 13,3% ) items with right criteria. Thus, the items made by biology class XII teachers are still suitable for final semester exam of the 2013/2014 academic year Sidrap Regency.